Multiple scattering simulation of electron channelling contrast images of dislocations at interfaces - Dudarev, S; Czernuszka, J; Peng, L; Wilkinson, A; Whelan, M (1995)
Quantum-mechanical multiple scattering theory of electron backscattering from crystalline materials is applied to simulate channelling images of dislocations situated near the surface of a crystal. A computational algorithm is developed which uses perturbation expansion of the solution of an inhomogeneous transport equation and which makes it possible to generate two-dimensional images of dislocations for various orientations of the Burgers vector. We compare the images simulated numerically with the results of experimental observations performed at inclined incidence using a conventional SEM and recently developed detector of backscattered electrons. The origin of the oscillations of the image intensity is discussed.